Productivity or discrimination? An economic analysis of excess-weight penalty in the Swedish labor market - Margareta Dackehag; Ulf-G. Gerdtham; Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2011)
Using longitudinal data, this paper investigates the penalty for excess weight in the Swedish labor market, distinguishing between the productivity and the discrimination hypotheses. We analyze employment, income, and sickness absence , using the latter as a direct measure of productivity. We find that excess weight women, but not men, experience a significant employment penalty. Both genders experience a significant income penalty for obesity. We conclude that the penalties are associated with lower productivity, primarily in terms of health. We find no evidence of discrimination.
Keywords: I10; I12; J23; J31; 330; Employment; income; sickness absence; obesity; overweight